Extreme weather and civil war in Somalia: Does drought fuel conflict through livestock price shocks? - Maystadt, Jean-François; Ecker, Olivier; Mabiso, Athur (International Food Policy Research Institute, 2013)
Climate change leads to more frequent and more intense droughts in Somalia. In a global context, weather shocks have been found to perpetuate poverty and fuel civil conflict. By relating regional and temporal variations in violent conflict outbreaks with drought incidence and severity, we show that this causality is valid also for Somalia at the local level. We find that livestock price shocks drive drought-induced conflicts through reducing the opportunity costs of conflict participation.